Review of Senior High School Mathematics Books for Grade X (2023 Revised Edition) on Exponents - Rosiani Feti Thanelab Nope; Nurhana Nurhana; Emi Anggriani; Muhammad Ammar Naufal (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study was conducted to comprehensively examine the presentation of exponents in the Grade 10 Mathematics textbook (Revised Edition 2023) published by the Ministry of Education, Culture, Research, and Technology. This study focuses on analyzing the structure of the concept map, alignment with national learning objectives, depth of material essence, relevance of the context used, and mapping the strengths and weaknesses of the textbook. A qualitative approach was used, employing content analysis through systematic documentation study. Research findings show that exponents are arranged coherently and hierarchically, and integrated with various real-life contexts, such as population growth, virus spread, and compound interest. This textbook encourages the development of higher-order thinking skills (HOTS) through the presentation of questions at the cognitive levels of analyzing (C4), evaluating (C5), and creating (C6) according to Bloom's Taxonomy. However, this study also found several important limitations, including inconsistencies between the material map and chapter content, particularly regarding the existence of logarithms, the density of material content that could potentially reduce the depth of student understanding, and the absence of explicit instructions and difficulty indicators for complex questions. Based on these findings, this study recommends the need to adjust the material map, separate the discussion of logarithms into a separate chapter, and add reflective guidance to exploration activities to support student independent learning in line with the spirit of the Merdeka Curriculum.